Leaf Epidermis of the Rheophyte Dyckia brevifolia Baker (Bromeliaceae) - Ghislaine Maria Lobo; Thaysi Ventura de Souza; Caroline Heinig Voltolini; Ademir Reis; Marisa Santos (The Scientific World Journal)
Some species of Dyckia Schult. f., including Dyckia brevifolia Baker, are rheophytes that live in the fast-moving water currents of streams and rivers which are subject to frequent flooding, but also period of low water. This study aimed to analyze the leaf epidermis of D. brevifolia in the context of epidermal adaptation to this aquatic plant’s rheophytic habitat. The epidermis is uniseriate, and the cuticle is thickened. The inner periclinal and anticlinal walls of the epidermal cells are thickened and lignified. Stomata are tetracytic, located in the depressions in relation to the surrounding epidermal cells, and covered by peltate trichomes. While the epidermal characteristics of D. brevifolia are similar to those of Bromeliaceae species, this species has made particular adaptations of leaf epidermis in response to its rheophytic environment.